Methyl Red Removal from Aqueous Solution by using Treated sugarcane bagasse - Saiful Azhar, Saad; Abdul Ghaniey Liew, Abdullah; Suhardy, Daud; Farizul Hafiz, Kasim; Mohd Nazry, Salleh (Institut Teknologi Bandung, 2008)
Organized by Institut Teknologi Bandung, 29th - 30th November 2006 at Institut Teknologi Bandung, Indonesia.